The effect of auricular acupuncture (AT4) when combined with electro-acupuncture in cerebral infarction recovery: A randomized trial - Ha, Tuong Phong; Nguyen, Thi Son; Le, Hoang Minh Quan; Nguyen, Hoai Thuong; Nguyen, Thi Ngoc Nghia; Ho, Thuc Anh; Nguyen, Thi My Phuong; Le, Ngoc Bao (Tạp chí Y Dược Huế, 2025)
Background and Objectives: Cerebral infarction can lead to severe consequences. According to traditional medicine theory, electro-acupuncture and ear acupuncture are some of the successful treatments for rehabilitating the motor functions of paralyzed limbs. The goal of this study is to evaluate the efficacy of combining ear acupuncture (AT4) with traditional electro-acupuncture to aid in the recovery of individuals experiencing limb paralysis due to a brain infarction. Methods: Patients at the Traditional Medicine Hospital in Ho Chi Minh City provided 108 samples for a clinical experiment. The research follows a randomized, unblinded, and controlled design. The evaluation criteria include the number of rounds the patient puts into the hole in 1 and 3 minutes, the time to walk 10 meters with support equipment, and the Barthel index (BI) score in 4 weeks. Results: The number of rounds the patient puts into the hole in 1 minute and 3 minutes increased, while the time to walk 10 meters with support equipment decreased. The difference from the baseline demonstrated the effectiveness of acupuncture in general and presented the results of combining acupuncture and ear acupuncture in particular. Compared to the two Groups, BI scores in the Treatment Group improved more than in the Control Group with a statistically significant difference. No patient had any adverse events during the study. Conclusion: Combining auricular acupuncture and electro-acupuncture can improve motor rehabilitation in patients with cerebral infarction.